Development and characterization of metal oxide nanoparticles for the delivery of anticancer drug. (17th February 2016) - Sharma, Harshita; Kumar, Krishan; Choudhary, Chetan; Mishra, Pawan K.; Vaidya, Bhuvaneshwar
Abstract : The aim of the study was to prepare chemotherapeutic agent-loaded zinc oxide nanoparticles for the intracellular delivery of drug, for better therapeutic activity. Zinc oxide nanoparticles have inherent anticancer properties, hence it was envisaged that by loading the anticancer drug into zinc oxide nanoparticles, enhanced anticancer activity might be observed. Zinc oxide nanoparticles were prepared using zinc nitrate and sodium hydroxide. Starch was used as the stabilizing agent. The nanoparticles prepared were characterized for size, shape, entrapment efficiency, and drug release. Further, cell line studies were performed to evaluate cellular uptake and cytotoxicity profile using MCF-7 cells. A hemolysis study was performed to check the acute toxicity of the nanoparticles. The nanoparticles were found to be 476.4 ± 2.51 nm in size, with low PDI (0.312 ± 0.02) and high entrapment efficiency (> 85%). The nanoparticles were stable, and did not form aggregates on storage in the dispersed form. A cytotoxicity study demonstrated that drug-loaded zinc oxide nanoparticles exhibited higher anticancer activity as compared to either blank zinc oxide nanoparticles and doxorubicin (DOX) alone, or their mixture. A hemolytic test revealed that the prepared zinc oxide nanoparticles caused negligible hemolysis. Thus, it can be concluded that zinc oxide nanoparticles loaded with DOX resulted in better uptake of the chemotherapeutic agent, and at the same time, showed low toxicity towards normal cells.